Delivery of Phosphorescent Anticancer Iridium(III) Complexes by Polydopamine Nanoparticles for Targeted Combined Photothermal‐Chemotherapy and Thermal/Photoacoustic/Lifetime Imaging. Issue 10 (15th August 2018) - Zhang, Dong‐Yang; Zheng, Yue; Zhang, Hang; Sun, Jing‐Hua; Tan, Cai‐Ping; He, Liang; Zhang, Wei; Ji, Liang‐Nian; Mao, Zong‐Wan
Abstract: Recently, phosphorescent iridium complexes have demonstrated great potential as anticancer and imaging agents. Dopamine is a melanin‐like mimic of mussel adhesive protein that can self‐polymerize to form polydopamine (PDA) nanoparticles that demonstrate favorable biocompatibility, near‐infrared absorption, and photothermal effects. Herein, PDA nanoparticles are functionalized with β‐cyclodextrin (CD) substitutions, which are further assembled with adamantane‐modified arginine‐glycine‐aspartic acid (Ad‐RGD) tripeptides to target integrin‐rich tumor cells. The thus formed PDA‐CD‐RGD nanoparticles can deliver a phosphorescent iridium(III) complexes LysoIr ([Ir(ppy)2 (l )]PF6, ppy = 2‐phenylpyridine, L = (1‐(2‐quinolinyl)‐β‐carboline) to form a theranostic platform LysoIr@PDA‐CD‐RGD. It is demonstrated that LysoIr@PDA‐CD‐RGD can be applied for targeted combined cancer photothermal‐chemotherapy and thermal/photoacoustic/two‐photon phosphorescence lifetime imaging under both in vitro and in vivo conditions. This work provides a useful strategy to construct multifunctional nanocomposites for the optimization of metal‐based anticancer agents for further biomedical applications. Abstract : β‐cyclodextrin‐functionalized polydopamine nanoparticles are loaded with an anticancer phosphorescent iridium(III) complex to form a multifunctional nanohybrid. The nanohybrid can further assemble with adamantane‐modified arginine‐glycine‐aspartic tripeptides targeting integrin‐rich tumors for highly effective combined photothermal‐chemotherapy and thermal/photoacoustic/two‐photon phosphorescence lifetime imaging.